Foundations of evidence law - Stein, Alex (Oxford University Press, 2005)
This is the first book to systematically examine the underlying theory of evidence in Anglo-American legal systems. Stein develops a detailed and innovative theory which sets aside the traditional vision of evidence law as facilitating the discovery of the truth. Combining probability theory, epistemology, economic analysis, and moral philosophy, he argues instead that the fundamental purpose of evidence law is to apportion the risk of error in conditions of uncertainty